2022
DOI: 10.1088/2057-1976/ac4d04
|View full text |Cite
|
Sign up to set email alerts
|

Personalized 3D-printed anthropomorphic whole-body phantom irradiated by protons, photons, and neutrons

Abstract: The objective of this study was to confirm the feasibility of three-dimensionally-printed (3D-printed), personalized whole-body anthropomorphic phantoms for radiation dose measurements in a variety of charged and uncharged particle radiation fields. We 3D-printed a personalized whole-body phantom of an adult female with a height of 154.8 cm, mass of 90.7 kg, and body mass index of 37.8 kg/m2. The phantom comprised of a hollow plastic shell filled with water and included a watertight access conduit for position… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 56 publications
0
3
0
Order By: Relevance
“…To overcome this limitation, QA solutions for novel workflows are machined from slabs of well-characterized surrogate materials [12,13] or use conventional phantoms modified, for example, by drilling holes to access the nasal cavities and change their filling [14]. On the other hand, additive manufacturing (AM), more commonly known as 3D printing, has gained traction as a way to enable quick and economical production of phantom components [15][16][17]. In recent years, commercial solutions for individualized, 3D-printed phantoms for photon therapy have entered the market [18,19], but their transferability to particle application is limited [20].…”
Section: Introductionmentioning
confidence: 99%
“…To overcome this limitation, QA solutions for novel workflows are machined from slabs of well-characterized surrogate materials [12,13] or use conventional phantoms modified, for example, by drilling holes to access the nasal cavities and change their filling [14]. On the other hand, additive manufacturing (AM), more commonly known as 3D printing, has gained traction as a way to enable quick and economical production of phantom components [15][16][17]. In recent years, commercial solutions for individualized, 3D-printed phantoms for photon therapy have entered the market [18,19], but their transferability to particle application is limited [20].…”
Section: Introductionmentioning
confidence: 99%
“…Differently from the Boron Neutron Capture Therapy (BNCT) exploiting thermal and epithermal neutrons to induce (n, a) reactions in boron carriers injected into patients 5,6,7 , the fast neutrons interact directly and efficiently with the hydrogen nuclei, producing recoil protons that ionize the tissues. Monte Carlo simulations have shown that the nIORT® delivers on the tumour bed a fast-neutron IR with a high linear energy transfer (LET) 8 and a relative biological effectiveness (RBE) 9 significantly higher than all other IRs such as X-rays, electrons and protons, thus resulting very efficient in producing DNA double strand breaks (DSBs) of the cancer cells. 10 It is known that around 50% of the absorbed dose imparted by neutron collisions (between 0.1 and 70 MeV) is due the ionizing effect of elastically scattered recoil protons, mainly from hydrogen atoms present in water contained in living cells.…”
Section: Introductionmentioning
confidence: 99%
“…Although various studies addressing patientspecific printed phantoms have been published, 5,[11][12][13][14] only few studies have performed detailed comparisons to conventionally produced anthropomorphic phantoms. 1,2,15,16 In the latter studies, computed tomography (CT) values (given in Hounsfield units [HU]) of reference phantoms could be reproduced with sufficient accuracy.…”
Section: Introductionmentioning
confidence: 99%